DEVELOPMENT OF ENTREPRENEURSHIP CHARACTER IN THE NURUL IMAN FOUNDATION, DR. M. NATSIR - Sri Wulan Dari (LPPM Ekasakti University, 2022)
This article aims to describe the development of entrepreneurial character for students at the Nurul Iman Foundation, Pondok Pesantren Dr. M. Natsir Alahan Panjang. Besides that, it is also to identify the obstacles faced by the coaches of Islamic boarding schools in fostering the entrepreneurial character of students. The research used a qualitative approach with a descriptive method. The selection of research informants used purposive sampling (purposive sampling). Data were collected through observation, document analysis, and interviews. While the data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results showed that the development of entrepreneurial character at the Nurul Iman Foundation, Pondok Pesantren Dr. M. Natsir is fostered through two organizations at Islamic Boarding Schools, namely KIR (Scientific Activities for Youth) and Agro-Business. As for the efforts made by the two organizations, namely providing habits such as: holding entrepreneurship seminars, utilizing plants on agro-business land for basic necessities and food businesses in cooperatives, collaboration between two organizations, facilities and infrastructure are used properly. Besides, the subjects of Craft and Entrepreneurship have been applied as compulsory subjects for elementary to high school. Entrepreneurship development is still not optimal because it has obstacles faced by the two organizations as follows: business capital, student participation and incomplete facilities and infrastructure.